The Green Ring of Tradition and Culture in Łódź as an example of a strategic plan to protect and shape the landscape of a former industrial city - Maria Dankowska (Ochrona Dziedzictwa Kulturowego, 2023)
Natural and cultural heritage co-create the cultural landscape, forming the basis of both local and larger sense of identity. Therefore, protecting and shaping these resources is the major task of currently living generations. It is possible and appropriate to undertake integrated action to protect and shape both natural and cultural heritage together. At the same time, it is important to take into account the specificity of these resources so as to ensure parallel development of both systemic solutions and specialized ones. The Green Ring of Tradition and Culture is a design proposal for asystem of attractive spaces surrounding the city centre of Łódź, which takes into account green areas, such as parks and allotment gardens, as well as greenery along the rivers Łódka and Jasień, cemeteries and post-industrial buildings: factories, residences and factory owners’ villas, and palaces or other culturally significant architectural objects of importance for the history of Łódź. A special place in this layout is held by Piotrkowska Street together with adjacent buildings – a defining component in the layout, which cuts across it and connects all other elements. The Green Ring in Łódź is currently not implemented but could utilize that utilizes the existing, significant potential of Łódź to create an attractive system of public spaces, thus highlighting and preserving the most valuable elements of the city’s cultural and natural heritage.